2015
DOI: 10.1026/1616-3443/a000298
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analyse zur Wirkung familienbezogener Präventionsmaßnahmen in Deutschland

Abstract: Theoretischer Hintergrund. In Deutschland wird eine Vielzahl von Programmen angeboten, die Eltern bei der Wahrnehmung ihrer Erziehungsaufgaben unterstützen und kindlichen Erlebens- und Verhaltensproblemen vorbeugen sollen. Internationale Befunde bescheinigen derartigen Maßnahmen positive Effekte, insbesondere bei kurzem Follow-up. Inwieweit die primär anglo-amerikanischen Ergebnisse auf andere Länder übertragen werden können, ist aber weitgehend unklar. Fragestellung. Der Beitrag berichtet über eine Meta-Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…Compared with mere child skills training, these comprehensive "packages" of programs are more promising, but they are also more expensive, more difficult to implement, and more challenging for evaluation. For example, family-oriented prevention programs showed similar effect sizes to child-oriented programs (e.g., [2,4,8]). Therefore, one can expect that combinations of such programs may be more effective than single programs by themselves.…”
Section: Moderator Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with mere child skills training, these comprehensive "packages" of programs are more promising, but they are also more expensive, more difficult to implement, and more challenging for evaluation. For example, family-oriented prevention programs showed similar effect sizes to child-oriented programs (e.g., [2,4,8]). Therefore, one can expect that combinations of such programs may be more effective than single programs by themselves.…”
Section: Moderator Effectsmentioning
confidence: 94%
“…Based on the findings of longitudinal research, numerous programs have been implemented in families, kindergartens, (pre)schools, family education centers, child guidance clinics, neighborhoods, youth justice institutions, and other contexts to prevent children from embarking on a life of crime [1,4]. The mean effects of these early developmental prevention programs have been positive [3,[5][6][7][8]. Indeed, in a comprehensive review of meta-analyses, Farrington et al [2] found desirable average effects for family-based, school-based, individually focused, and general prevention programs.…”
Section: Introductionmentioning
confidence: 99%
“…Zur Bedeutung der Familie für die psychosoziale Entwicklung von Kindern liegen zahlreiche Studien vor: Eine sichere Bindung, ein autoritativer Erziehungsstil und ein gutes Familienklima sowie anregende Interaktions-/Kulturpraktiken ermöglichen Kindern nachweislich kurz-und langfristig einen erfolgreichen Umgang mit normativen Entwicklungsaufgaben sowie kritischen Lebensereignissen (Hohm et al, 2017;Werner & Smith, 1982). An diesen Faktoren ansetzende Familienbildungsprogramme und Elterntrainings erzielten insgesamt gute Evaluationsergebnisse (Beelmann & Schulz, 2013;Weiss, Schmucker & Lösel, 2015) Wild & Walper, 2020). Der Einfluss des Elternhauses im Bereich der schriftsprachlichen Entwicklung von Kindern ist ebenfalls vielfach nachgewiesen (Hurrelmann, 2004;McElvany, Becker & Lüdtke, 2009).…”
Section: Die Familie Als Ort Der Informellen Bildungunclassified
“…Verglichen mit den für familienbezogene Präventionsprogramme gefundenen, zumeist mittleren Effekten (z. B. für Erziehungsverhalten; Weiss et al, 2015;Nowak & Heinrichs, 2008) Beelmann (2006) in vorhandene Versorgungssysteme eingebracht werden kann, gilt es zuvor das Training mitsamt der verwendeten Materialien so aufzubereiten, dass es auch von Fachkräften in der Praxis durchführbar ist. Zudem ist der Implementationsprozess wissenschaftlich zu begleiten, um eine qualitativ hochwertige Umsetzung zu gewährleisten (Fries & Souvignier, 2009).…”
Section: Limitationen Und Ausblickunclassified
“…have proven to be effective (Furlong et al, 2012;Nowak & Heinrichs, 2008;Piquero et al, 2016;Sandler, Schoenfelder, Wolchik & MacKinnon, 2011;Stattin, Enebrink, Özdemir & Giannotta, 2015;Weiss, Schmucker & Lösel, 2015;Weisz & Kazdin, 2010) and are regarded as the gold standard in the field of prevention of behavioral problems in children (United Nations Office on Drugs and Crime, 2009;World Health Organization, 2009). In a meta-analysis, which comprised 77 trials about parent trainings with different theoretical orientations, Kaminski, Valle, Filene and Boyle (2008) reported a low effect size (d) of 0.34 (95% confidence interval [0.29; 0.39]).…”
Section: Parenting Skills Courses Especially Cognitive-behavioral Pamentioning
confidence: 99%